Biomarkers of Alzheimer's disease in mild cognitive impairment: Experience in a memory clinic from Latin America - Allegri, Ricardo Francisco (2014)
Objective: This study aimed to investigate the role and prognosis of Alzheimer disease biomarkers in patients with mild cognitive impairment (MCI) at a memory clinic in Latin America. Methods: We studied 89 patients with MCI, 43 with Alzheimer-type dementia, and 18 healthy controls (matched for age, sex, and educational level) at our memory clinic (Instituto FLENI) in Buenos Aires, Argentina. Patients and controls underwent an extensive demographic, neurological, and neuropsychological assessment. All subjects underwent a brain MRI scan; FDG-PET scan; amyloid PET scan; apolipoprotein E genotyping; and cerebrospinal fluid concentrations of Aβ1-42, tau, and phosphorylated tau. Patients were categorised as positive or negative for the presence of amyloid pathology and neurodegeneration. Results: Amyloid pathology was observed in cerebrospinal fluid results in 18% of controls, 64% of patients with MCI, and 92% of patients with Alzheimer-type dementia. Suspected non–Alzheimer disease pathophysiology was found in 11% of controls, 6% of patients with MCI, and 8% of patients with Alzheimer-type dementia. At 30 months of follow-up, 45% of amyloid-positive patients with MCI and 20% of amyloid-negative patients with MCI showed progression to dementia. Conclusions: This study demonstrates biomarker-based MCI prognosis and supports its role in clinical decision-making in daily practice.